How COVID-19 Pandemic Bolsters China’s Influence Toward Hegemonic Race In ASEAN? - Rusli, Andi Ibnu Masri (Nation State: Journal of International Studies, 2021)
The Covid-19 outbreak that occurred at the end of 2019 added to a long series of global crises at a time when the trade war was still ongoing. The epidemic then quickly spread throughout the world. Southeast Asia is no exception. The presence of this epidemic in Southeast Asia adds to the intensity of the struggle for hegemony between the United States and China. Vaccine diplomacy from China, the United States, and ASEAN itself presents its own dynamics for the competition for hegemony in this region from the two countries. This paper uses a qualitative method approach, where the author presents a critical review of the current dynamics. While the theoretical basis, the author uses the theory of hegemony through non-traditional security approach instruments centered on the vaccine diplomacy competition conducted by two superpower countries. The results show how the dynamics of the superiority of China's vaccine diplomacy are important points and provide broad projections of a new chapter in the struggle for hegemony in Southeast Asia.